The contribution of organizational commitment and work climate to the work productivity of public elementary school teachers - Yuharnis, Yuharnis; Susanti, Lusi; Gistituati, Nurhizrah; Sabandi, Ahmad (Universitas Jambi, Indonesia, 2026)
Teacher productivity is an important factor in achieving educational goals and improving school performance. This study examined the contributions of organizational commitment and work climate to the work productivity of public elementary school teachers in West Pasaman Regency, Indonesia. A quantitative correlational design was employed involving 397 civil servant teachers selected through cluster and stratified random sampling. Data were collected using a validated questionnaire and analyzed using descriptive statistics and multiple regression. The findings showed that organizational commitment contributed 51.2% to teacher productivity, while work climate contributed 38.0%. Together, both variables explained 55.2% of the variance in productivity. Organizational commitment emerged as the stronger predictor. The results suggest that teachers who feel attached to their schools and work in supportive environments are more likely to perform effectively. Strengthening teacher commitment and fostering a positive work climate may therefore help improve teacher productivity and educational quality.